The introduction of the concept of anxiety into China: a thematic historical study - Miao, Peng (Frontiers in Psychology, 2024)
Introduction This article presents a thematic historical study on the introduction of “anxiety” to modern China. Based on seminal research conducted previously by European scholars on histories of psychological and psychiatric concepts, this article reviews the itinerary of “anxiety” to China by using multiple types of textual evidence. Alongside a detailed description of how “anxiety” was translated and introduced, a comparison between the notions of “anxiety” in Traditional Chinese Medicine (TCM) and Western psychoanalytic approaches was made. The processes of how “depression” and “anxiety” were introduced to China were also compared. Materials and methods Three types of textual evidence were meticulously analyzed. First, lexicographical works published since the 19th century were examined to trace the initial introduction and observe the standardized translation of “anxiety” in Chinese. Second, newspaper and periodical articles were analyzed to understand how knowledge of “anxiety” was communicated to the general public. Third, the evolution of psychological and psychiatric terminologies was observed through medical books. Results It was found that “anxiety” was initially translated into various Chinese terms, with “jiaolyu” eventually emerging as the standardized term after 1949. The textual evidence showed that “anxiety” began to be acknowledged as a disease concept in the early 20th century, though it was not formally recognized as a diagnostic category until the late 20th century. This article also highlights the differences between the Western psychoanalytic view on anxiety and the Chinese folk conception of it. Discussion and conclusions It was observed that the introduction processes of depression and anxiety to China were similar, though their conceptual histories in the West showed much difference. The fading of neurasthenia marked a new era of psychiatric development in China, characterized by an enhanced specificity in the classification of mental disorders, which was never observed in the discourse about “xin feng,” a corresponding TCM notion of “anxiety.” The article also underscores the need for further exploration of corresponding TCM concepts of “anxiety” and the assimilation of Western psychiatric concepts in China.